DEVELOPMENT OF EARTHWORM (LUMBRICUS RUBELLUS) PROTEIN HYDROLYSATE FRACTION: STUDY OF NEUROPROTECTIVE EFFECTS, EX VIVO GASTROINTESTINAL STABILITY, AND TABLET FORMULATION ORIENTATION - Natassya Mercy Hadiwijaya, Ruth
Peripheral neuropathy, an idiopathic or acquired condition stemming from other ailments, deteriorates quality of life through somatosensory disturbances, with current therapeutic regimens remaining largely symptomatic. Earthworm (Lumbricus rubellus) protein hydrolysate fractions emerge as promising candidates for regenerative therapy in peripheral neuropathy. Their in vitro mechanism involves inducing NGF expression, which enhances Schwann cell proliferation in the face of nerve damage. This study aimed to develop earthworm (Lumbricus rubellus) protein hydrolysate fractions for systemic effects by evaluating their stability profile using Tricine-SDS PAGE, assessing their in vivo activity in a Chronic constriction injury model at doses of 50, 100, and 200 mg/kg BW, and exploring tablet formulation strategies. Thermal hydrolysis produced protein hydrolysate fractions with five characteristic protein bands at sizes of ±21 kDa, ±19 kDa, ±17 kDa, ±14.2 kDa, and ±6.5 kDa. Each protein band underwent degradation by gastrointestinal enzymes, particularly intestinal enzymes, with maximum degradation reaching 61.457% in gastric fluid, 91.297% in intestinal fluid, and 48.302% in colonic fluid. All three doses exhibited neuroprotective effects in the animal model, demonstrating a significant difference from the negative control group (p-value < 0.05). No significant differences were observed in the effects between doses (p-value > 0.05). Histopathological analysis corroborated these findings, revealing an increase in Schwann cell density and a reduction in neuronal gaps. Optimum tablet formulation is wet granulation tablets with 1% aerosil adsorbent of the active ingredient weight.